Differentiate y = xe^(2x).

We want to find dy/dx. We find this using the product rule by setting the functions f(x) = x and g(x) = e2x. With these functions, we can write the equation as y = f(x)g(x), so by applying the product rule, we have that dy/dx = f'(x)g(x) + f(x)g'(x). To calculate g'(x), we use the chain rule.If we write h(x) = 2x, then g(x) = e2x = eh(x). So by using the chain rule and the fact that ex differentiates to itself, we have that g'(x) = h'(x)eh(x) = 2e2x. Therefore by going back to the equation which we found by the product rule, dy/dx = f'(x)g(x) + f(x)g'(x) = (1)(e2x) + (x)(2e2x) = e2x + 2xe2x. We can factorise this to get dy/dx = (1 + 2x)e2x.

Answered by Matthew L. Maths tutor

25307 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve has parametric equations x=t(t-1), y=4t/(1-t). The point S on the curve has parameter t=-1. Show that the tangent to the curve at S has equation x+3y+4=0.


solve the equation 2cos x=3tan x, for 0°<x<360°


Express 3x+1/(x+1)(2x+1) in partial fractions


using the substitution u=6-x^2 integrate (x^3)/(6-x^2)^1/2 with respect to x, between 1 and 2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences